Retributivism essays on theory and policy - White, Mark D., 1971- (New York ; Oxford : Oxford University Press, 2011)
The contributors offer analysis and explanations of new developments in retributivism, the philosophical account of punishment that holds that wrongdoers must be punished as a matter of right, duty, or justice, rather than deterrence, rehabilitation, or vengeance.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Includes bibliographical references and index.
Keywords: Punishment -- Philosophy; Retribution